Grey relation projection model for the ecological sensitivity - ZHAO Xiao-hui; YAN Li-jiao (浙江大学学报. 农业与生命科学版)
Ecological sensitivity analysis is an important foundation of ecological city planning. Because of the complexity and relative factors' diversity in a region, many evaluation methods are being gradual explored and improved. Environment system is almost a grey system owing to the unascertained and imcomplete information of relative factors. A grey relation projection model for ecological sensitivity analysis was established based on grey system theory and vector projection principle. In the model, evaluated samples and classified standards were treated as vector, which projected on the same ideal samples. Then, evaluated samples were classified and arranged according to the projective value. As a case, the grey relation projection model, based on the established criteria and standards of ecological sensitivity evaluation, was used to assess the ecological sensitivity of Anji County. The result shows that this model is scientific and effective for ecological sensitivity evaluation.